From Slash and Burn to Replanting : Green Revolutions in the Indonesian Uplands? - Ruf, François; Lançon, Frederic (Washington, DC: World Bank, 2013)
The most traditional and widely used farming systems in the humid upland tropics are based on fallowing and various forms of slash-and-burn agriculture. Their sustainability depends on the duration of the fallow; as long as the fallow stage is longer than seven or eight years, slash-and-burn systems usually remain efficient. They produce a moderate yield using a low-input technology that is especially efficient in terms of returns to labor. With a few exceptions, yield per hectare and labor returns decline when fallow duration drops below the threshold of seven or eight years. This decline can be interpreted as the loss of the "forest rent," one of the main concepts used in this study. Forest rent also applies to most perennials, which despite their name are often managed under a kind of shifting cultivation. As coffee, cocoa, and even rubber farms are sometimes abandoned to "fallow" and replanted later on, a tree crop system may well be considered as an extended form of shifting cultivation, hence the concept of tree crop shifting cultivation used in this study. If the coffee or cocoa farms are not abandoned for several years to enable a regrowth of a secondary forest, replanting is more difficult or more costly than initial planting. Yields and revenues can be expected to be lower. This decline of revenues and increase of costs matches the concept of the loss of forest rent.